Role of Soft Skills and Personality Development in Teacher Education - A. , Thangam; M. , Rengarajan; K. , Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Personality development is significant in aiding the evolution of student-teachers in teacher training programs. It incorporates the acquisition of soft skills such as ethical behavior, language learning, professionalism, body language, class management, pedagogy, and practice of legal matters while staying informed and up-to-date with current news and technology. These are climacteric and holistic skills that teachers not only require but also tremendously lack in developing countries to this day. Training such as this one could spark the desire inherent in younger teachers. It helps them bring out their intellectuality, impacts their sphere positively, and strengthens their coping mechanism during work pressure. Learners benefit when they adopt influence over professional and social circles that help them further their careers. Every individual yearns to harbor and demonstrate certain values and skills before embarking on career-driven adventures. It is their right to have complete control over their profession without missing out on personal and workplace values. Educational institutions foster an ever-growing demand for such courses that refine aspirants and groom them for interviews, seminars, and discussions. It takes any foundation to the future of advanced learning. Personality development is the foremost requirement for any qualified teacher that is independent. The skills it instills become requisite for sharing ideas and for carrying out beneficial interaction, be it between students and teachers or parents and teachers.